The Knowledge, Attitudes, and Practices of Healthy Eating Questionnaire: a pilot validation study in Chinese families - Kiki S. N. Liu; Julie Y. Chen; Julie Y. Chen; Kai-Sing Sun; Joyce P. Y. Tsang; Joyce P. Y. Tsang; Patrick Ip; Carlos K. H. Wong; Carlos K. H. Wong; Carlos K. H. Wong; Carlos K. H. Wong; Cindy L. K. Lam; et al. (Frontiers Media S.A., 2024)
IntroductionIdentifying the knowledge, attitudes, and practices (KAP) gaps of healthy eating can inform the design of effective interventions. This study aimed to test the validity and psychometric properties of a KAP of Healthy Eating Questionnaire (KAP-HEQ) tailored to the Chinese culture.MethodsThe dimensions and potential items of each KAP scale were identified from published KAP and health literacy questionnaires, which were supplemented by the findings of a previous qualitative healthy eating study. Content validity of the KAP-HEQ was evaluated by eight experts and eight Chinese parent-adolescent dyads in Hong Kong through content validity ratio (CVR), content validity index (CVI), and qualitative feedback. The feasibility, construct validity, reliability, and sensitivity of the KAP-HEQ were evaluated in this pilot study among 60 adolescent-parent dyads (120 persons) through an online survey. The first 30 dyads who completed the KAP-HEQ were invited to repeat the KAP-HEQ 2 weeks later to assess the test-retest reliability.ResultsThe final 44-item KAP-HEQ was completed in 10-15 min by both adolescents and their adult parents. The CVR ranged from −0.38 to 1, and the CVI ranged from 0.56 to 1. Over 80% of the items achieved convergent validity (a significantly positive correlation with its hypothesized scale) and discriminant validity (a higher correlation with its hypothesized scale than with the other two scales). Cronbach's alpha for the internal consistency of the Overall, Attitude, and Practice scales was >0.7, while that of the Knowledge scale was 0.54. The intraclass correlation coefficient (ICC) on test-retest reliability of the Overall and individual scales were all >0.75 except that of the Knowledge scale (ICC = 0.58). The significant differences in KAP scale scores with small to large effect sizes were found between known groups as hypothesized, except the Attitude score between groups by household income, which supported the sensitivity of the KAP-HEQ.ConclusionThe KAP-HEQ has shown good validity, reliability, and sensitivity among Chinese adolescents and adults, which can be applied to evaluate KAP status and gaps to inform the design and assess the effectiveness of healthy eating interventions.